2009
DOI: 10.1111/j.1399-3054.2009.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Intron polymorphism pattern in AOX1b of wild St John's wort (Hypericum perforatum) allows discrimination between individual plants

Abstract: The present paper deals with the analysis of natural polymorphism in a selected alternative oxidase (AOX) gene of the medicinal plant, St John's wort. Four partial AOX gene sequences were isolated from the genomic DNA of a wild plant of Hypericum perforatum L. Three genes belong to the subfamily AOX1 (HpAOX1a, b and c) and one to the subfamily AOX2 (HpAOX2). The partial sequence of HpAOX1b showed polymerase chain reaction (PCR) fragment size variation as a result of variable lengths in two introns. PCR perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 73 publications
(84 reference statements)
2
26
0
Order By: Relevance
“…Overall, multiple sequence alignment has shown that they were homologous to each other and comprised conserved exon regions at two end positions and non-conserved or variable intron region in the middle. Similar kind of observation was also reported in rice, 18 Hypericum perforatum 31 and foxtail millet. 20 Further, higher level of transferability of ILPs compared with previously identified markers reflects the conserved nature of exon positions in gene and variability in the non-coding sequences.…”
Section: Resultssupporting
confidence: 86%
“…Overall, multiple sequence alignment has shown that they were homologous to each other and comprised conserved exon regions at two end positions and non-conserved or variable intron region in the middle. Similar kind of observation was also reported in rice, 18 Hypericum perforatum 31 and foxtail millet. 20 Further, higher level of transferability of ILPs compared with previously identified markers reflects the conserved nature of exon positions in gene and variability in the non-coding sequences.…”
Section: Resultssupporting
confidence: 86%
“…Induced single nucleotide polymorphism (SNP) was shown to affect a quantitative trait locus (QTL) for thermo tolerance in Oryza sativa L. (Abe et al 2002). AOX genes demonstrate a rich natural source for polymorphic within‐gene sequences in various species that might be explored in the future for functional marker candidates (Cardoso et al 2009, Ferreira et al 2009, Holtzapffel et al 2003, Macedo et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2). These observations suggest that defined SNPs appear rather non‐casually in pre‐determined positions as it was also found in D. carota (Cardoso et al 2009), O. europaea (Macedo et al 2009) and H. perforatum (Ferreira et al 2009), where repetitive polymorphisms were identified. Three of the six amino acid substitutions observed in the two Pp AOX1bs (positions 194, 195 and 244) also provide uniqueness to Pp AOX1b2 in otherwise conserved sites across species (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Recently, the group of Arnholdt‐Schmitt et al (2006) focussed on AOX functional marker development and naturally occurring evidence for across‐species AOX polymorphisms. Several cases of AOX polymorphisms have been highlighted, including intron length polymorphisms (ILPs) in Hypericum perforatum L. (St. John's Wort), Daucus carota L. and Vitis vinifera L. (Cardoso et al 2009, Costa et al 2009b, Ferreira et al 2009), synonymous and non‐synonymous SNPs in H. perforatum , D. carota and Olea europaea L. (Cardoso et al 2009, Ferreira et al 2009, Macedo et al 2009), micro heterogeneity through 3′‐untranslated region (UTR) length variability in O. europaea (Macedo et al 2009) and retrotransposon integration in an intron of AOX2 in V. vinifera (Costa et al 2009b). ILPs and SNPs observed in AOX genes demonstrate repetitive patterns and indicate non‐casual occurrence.…”
Section: Introductionmentioning
confidence: 99%